2017
DOI: 10.1016/j.sna.2017.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Polymer resonators sensors for detection of sphingolipid gel/fluid phase transition and melting temperature measurement

Abstract: This work describes a low-cost biophotonic sensor shaped by way of cheap processes as hybrid silicon/silica/polymer resonators able to detect biological molecule gel/fluid phase transition as lipids at very low concentration (sphingomyelin). The photonic structure is composed of specific amplified deep UV photoresist-polymer waveguides coupled by a sub-wavelength gap with racetrack microresonators allowing a low temperature-dependent operation ranging from 16 to 42 °C. The temperature dependent wavelength shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…[16]. On such devices, the thermal dependences of the main optical properties at the Si/SiO 2 /UV210/air configuration were presented, and it was concluded that the thermo-optical properties of the IO microresonator based on UV210 polymer have a high quality, verifying its high thermal stability [16]. Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…[16]. On such devices, the thermal dependences of the main optical properties at the Si/SiO 2 /UV210/air configuration were presented, and it was concluded that the thermo-optical properties of the IO microresonator based on UV210 polymer have a high quality, verifying its high thermal stability [16]. Fig.…”
Section: Resultsmentioning
confidence: 94%
“…From previous studies focused on the detection of gel/fluid phase transition of biological compounds using polymeric microcavity, an extended experimental and computing protocol were presented in ref. [16]. On such devices, the thermal dependences of the main optical properties at the Si/SiO 2 /UV210/air configuration were presented, and it was concluded that the thermo-optical properties of the IO microresonator based on UV210 polymer have a high quality, verifying its high thermal stability [16].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The fabrication of the structures is detailed. The experimental setup is presented and then relevant results on fatty acid [9] (cosmetic, food) and sphingomyelin [10] (biology) phase transitions are exposed and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…As miniaturizable and most accurate, photonic micro-resonator sensors come up as very efficient in following small-scale phenomena or in detecting sparsely concentrated chemical species [11]. These characteristics are most interesting for both environmental monitoring [12] and biology together with biomedical or biophysics [13] fundamental research (among other fields). However, with a large majority of scientific works using integrated micro-resonator sensors focusing on static phenomena [9,[11][12][13], most often the transduced signal of the photonic structure is monitored against concentration values of given species or versus temperature.…”
Section: Introductionmentioning
confidence: 99%